Analysing Macroeconomic Precarities in the South Asian Neighbourhood - Bhowmick, Soumya; Roy Bardhan, Arya (Journal of Emerging Markets and Management, 2025)
A global slowdown is impending as the post-pandemic recovery was overturned by the Russia-Ukraine war, worsening geopolitical strife and disruption of global value chains. Although the contractionary effect will be felt worldwide, the emerging economies of South Asia, rife with internal political struggle and economic turmoil, require scrupulous inspection. This paper analyses the series of events which culminated in the unmanageable economic state of affairs in Bangladesh, Pakistan, Nepal, Sri Lanka and Myanmar. It is found that despite the unique economic structure of each nation, there is a currency crisis in the offing or has already led to the collapse of each exchange rate. The disposition delves into those systemic and economic factors that inadvertently lead to currency crises and irrecoverable Balance of Payment deficits. The International Monetary Fund seems to be the short-term answer to the problem but long-term measures that structurally reform these economies are essential. This paper delves into the fault lines for such macroeconomic instabilities and suggests a few structural measures to circumvent economic shocks in the longer horizon. This paper provides a thorough analysis of the events and global circumstances during the COVID panedmic that led to the onset of a silent crisis in South Asia.